2017
DOI: 10.1021/acscatal.7b03086
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Level Insights into Oxygen Reduction Catalysis by Graphite-Conjugated Active Sites

Abstract: Using a combination of experimental and computational investigations, we assemble a consistent mechanistic model for the oxygen reduction reaction (ORR) at molecularly well-defined graphite-conjugated catalyst (GCC) active sites featuring aryl-pyridinium moieties (N + -GCC). ORR catalysis at glassy carbon surfaces modified with N + -GCC fragments displays near-first-order dependence in O 2 partial pressure and near-zero-order dependence on electrolyte pH. Tafel analysis suggests an equilibrium one-electron tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 86 publications
2
34
0
Order By: Relevance
“…It is difficult to simply compare the ORR catalytic activity of 5/AB with those of other catalysts such as heteroatom doped carbon [6][7][8][9][10][11][12][13][14][15][16][17][18] /graphene quantum dots [34][35][36][37] , because their electrode preparation methods, measurement conditions, and potential standard are different for each investigation. However, when these previous studies are overviewed as a whole, the E on ORR values are ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to simply compare the ORR catalytic activity of 5/AB with those of other catalysts such as heteroatom doped carbon [6][7][8][9][10][11][12][13][14][15][16][17][18] /graphene quantum dots [34][35][36][37] , because their electrode preparation methods, measurement conditions, and potential standard are different for each investigation. However, when these previous studies are overviewed as a whole, the E on ORR values are ca.…”
Section: Discussionmentioning
confidence: 99%
“…However, sufficient ORR catalytic activity was not obtained with these quinone-modified electrodes. In other cases, graphene quantum dots including a phenazine unit in the carbon framework has been recently reported to show high ORR catalytic activity [34][35][36][37] , though they were yet to be estimated at a small-molecule level, as is the case with other carbon fragment materials like g-C 3 N 4 . 38 The πconjugated polymers such as polyaryls 39 and poly(arylacenaphthenequinonediimine) 40 were reported to exhibit ORR catalytic activities.…”
mentioning
confidence: 99%
“…[109] Graphite-conjugated catalysts produced by conjugating N-doped molecular fragments on the surface of graphitic carbons have exhibited excellent ORR activities and the covalent molecule is reported to be electrocatalytically active for the ORR. [110,111] Combined DFT calculations and experimental results have revealed that the alpha electrophilic carbon atoms near the pyridinium-N moiety acted as active sites for O 2 adsorption and ORR electrocatalysis. Besides, chemisorption of polysulfides on a carbon fiber paper containing oxygen functional groups has been used for lithium-sulfur batteries.…”
Section: Chemical-adsorption-induced Charge Transfermentioning
confidence: 99%
“…Numerous methods have been developed to immobilize electrocatalysts at the surface of electrodes, through covalento r noncovalent interactions. These methods include using pstacking interactions, [20][21][22] click chemistry, [23][24][25] amine [26] or vinyl electropolymerization, [27] covalent attachment to graphite, [28,29] diazonium salts, [30][31][32][33] as well as silane and phosphonate linkers to oxidest on ame af ew of the most popular techniques. [34][35][36] The specific methods used are dictated by electrode material and tolerance of the electrocatalyst to graftingf unctional groups.The objective in most reports is the fabrication of catalyst-functionalized electrodes.…”
Section: Graftingone Lectrodesmentioning
confidence: 99%